1996
DOI: 10.1029/96wr02694
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Sorption and Displacement of Hydrophobic Organic Contaminants in Saturated Subsurface Soil Systems

Abstract: The sorption of tetrachloroethylene and trichlorobenzene by a subsurface soil that exhibits moderately nonlinear sorption isotherms for each solute was found to be strongly competitive, while that by a soil for which both solutes exhibit more linear sorption isotherms was essentially additive. The isotherm nonlinearity and competitive sorption observed in the former case suggest that a greater fraction of the sorption by that soil occurred on or within tightly ordered or condensed organic matrices rather than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 12 publications
1
31
0
Order By: Relevance
“…McGinley et al [21] observed competitive effects in a diagenetically old soil but not in an immature soil rich in amorphous organic matter.…”
Section: Discussionmentioning
confidence: 99%
“…McGinley et al [21] observed competitive effects in a diagenetically old soil but not in an immature soil rich in amorphous organic matter.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly accepted that sorption of organic compounds into organoclay are partitioning (dissolution) [35], and the characteristic of sorption isotherm is linear [36]. Moreover, parti- tioning shows no competition between solutes.…”
Section: Sorption Mechanismmentioning
confidence: 99%
“…In order to model these transport processes sorption equilibrium parameters are required. In the past, most of the published equilibrium studies were focused upon neutral organic substances, e.g., PAHs [1,2], polychlorinated biphenyls [3,4], monocyclic aromatic hydrocarbons [5,6], chlorinated benzenes [7], chlorinated aliphatic hydrocarbons [5Ϫ8].…”
Section: Introductionmentioning
confidence: 99%